2016
DOI: 10.15268/ksim.2016.4.3.069
|View full text |Cite
|
Sign up to set email alerts
|

School Violence Experience and Coping of Students with High Functioning Autism Spectrum Disorders in Inclusive Education Environment

Abstract: PURPOSE :The purpose of the this study was to build an understanding of school violence experiences among students with high functioning autism spectrum disorders(HF-ASD) in inclusive education environment and provide basic data to prevent and intervene it. METHOD :Sixteen mothers having a son with HF-ASD were interviewed in-depth and shared their son's experiences. The qualitative research method are used in the collection and analysis of data. RESULT :As a result of this research, 4 categories, 11 sub-catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“… 89 A Korean study also reported that victimization in students with other disabilities was more frequent in elementary schools (approximately 8–12 years) than in high schools (approximately 16–18 years). 90 Fewer comorbid conditions (e.g., internalizing and externalizing symptoms) in older children with ASD than in younger children with ASD, 91 along with more coping strategies developed with longer educational and social learning experiences, 92 might have resulted in such an age pattern.…”
Section: Discussionmentioning
confidence: 99%
“… 89 A Korean study also reported that victimization in students with other disabilities was more frequent in elementary schools (approximately 8–12 years) than in high schools (approximately 16–18 years). 90 Fewer comorbid conditions (e.g., internalizing and externalizing symptoms) in older children with ASD than in younger children with ASD, 91 along with more coping strategies developed with longer educational and social learning experiences, 92 might have resulted in such an age pattern.…”
Section: Discussionmentioning
confidence: 99%
“…For example, according to Park et al (15:911), the number of research articles on bullying autistic people by January 2018 in English, Japanese, and Korean was 752, 227, and 20, respectively, which shows that academic concern lags in terms of the number of articles. Despite many researchers interested in autism in these countries, Korean articles focused on either autistic persons' parents (32)(33)(34) or literature analysis (35) and quantitative analysis (36). The status proves the need for research on what is happening in the school life of autistic persons, especially on school violence against autistic pupils in their own words.…”
Section: Introductionmentioning
confidence: 99%